Relation of Variable of Communication and Adaption Capacity of Rice Farmer on Clmate Change (Case of Pasuruan Regency, East Java) - Yudi L.A Salampessy; Djuara P. Lubis; Le Istiqlal Amien (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
As a seasonal crop, rice production is highly depend on the carrying capacity of the climate, that the changing climate requires the adaptive capacity of the farmers. On the other hand, climate change is still a new and complex issue for most people which is followed by differences in response to its impact. This research tries to describe the relationship between communication variables and adaptive capacity to climate change of rice farmers. The survey method is applied in lowland, midland, and upland agroecosystem zones affected by climate change which are represented by 32 rice farmers each. The result shows that there is a very strong relation between climate change communication variables of the farmers and their capacity in adapting to the climate change. Therefore, the diversity of sources of climate change information of the farmers and the frequency of its use, and the exposure to climate change information and convergence of climate change communication of the farmers need to be improved.